Circulatory Support for High-Risk Coronary Artery Bypass Grafting and Coronary Interventions: Where is the Evidence? - Gorton, Andrew J.; Keshavamurthy, Suresh (International Journal of Angiology, 2025)
Coronary artery disease remains the leading cause of morbidity and mortality worldwide. Patients with ischemic cardiomyopathy or other high-risk features undergoing coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) present significant perioperative challenges due to elevated procedural risks. Mechanical circulatory support (MCS) devices such as the intra-aortic balloon pump, Impella devices, and venoarterial extracorporeal membrane oxygenation have increasingly been used to mitigate these risks. This review aims to evaluate the evidence supporting the use of temporary MCS in high-risk CABG and PCI, define high-risk patient populations, and compare device-specific benefits, risks, and clinical outcomes.
Keywords: coronary artery disease; percutaneous coronary intervention; coronary artery bypass grafting; mechanical circulatory support